The Effectiveness of Group Guidance Using Film Media and Assignment Technique to Develop Students Respect Attitude (Jurnal Bimbingan Konseling, 2019)
Respect attitude must grow among students in a classroom or environment. It is aimed at good communication without distinguishing any differences. This study attempted to examine the effectiveness of group guidance using Film Media and Assignment Technique to develop the respect attitude of the students of Senior High School Gemuh Kendal. The method used was experimental with Randomized Pre-test - post-test comparison group design. This involved as many as 21st Grade Students of Natural Science Department of Senior High School Gemuh Kendal as the subject of the study. Further, the analysis results by using One Way ANOVA showed that the group counseling using film media and assignment technique was effective to develop students’ respect attitude (F = 78.141; p < 0.01). At last, the discussion of the findings of this study was directed at looking at the effectiveness of the film media group guidance and assignment technique group guidance.